2003
DOI: 10.1562/0031-8655(2003)078<0355:tcomma>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Tight Control of Matrix Metalloproteinase-1 Activity in Human Skin¶

Abstract: Chronic ultraviolet irradiation leads to photoaging in human skin, which is associated with degradation of connective tissue. This is partly due to the fibroblast collagenase (matrix metalloproteinase 1 [MMP-1]). Using complementary DNA array technique we demonstrate that after UV irradiation, MMP-1, MMP-3 and the tissue inhibitor of matrix metalloproteinase 1 (TIMP-1) are time-dependently induced on the messenger RNA level in dermal fibroblasts in vitro and in vivo in human buttock skin. This increase in gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 21 publications
2
30
0
1
Order By: Relevance
“…We observed that MMP-1 mRNA expression was activated within 24 h after UVB irradiation followed by a decline to the level in cells (not shown data). Südel et al 2) reported that after UV irradiation, MMP-1 was time-dependently induced on the mRNA level in dermal fibroblasts in vitro/in vivo in human skin and then a strong induction of MMP-1 mRNA at 24 h after UV irradiation as similar as our results. We also found that UVB-induced MMP-1 mRNA expression showed a negative relationship with fucoidan levels followed by a 24 h incubation period.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…We observed that MMP-1 mRNA expression was activated within 24 h after UVB irradiation followed by a decline to the level in cells (not shown data). Südel et al 2) reported that after UV irradiation, MMP-1 was time-dependently induced on the mRNA level in dermal fibroblasts in vitro/in vivo in human skin and then a strong induction of MMP-1 mRNA at 24 h after UV irradiation as similar as our results. We also found that UVB-induced MMP-1 mRNA expression showed a negative relationship with fucoidan levels followed by a 24 h incubation period.…”
Section: Discussionsupporting
confidence: 91%
“…Südel et al 2) suggested that time after UV exposure in vitro directly determines the extent of damage that is inflicted on MMP-1 expression. Di Girolamo et al 18) reported that MMP-1 expression increases both as a function of time and dose in cultured cells in response to UV exposure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Suction blisters were obtained from the volar forearms of 10 healthy male volunteers, as described previously [40]. Suction blister roofs were taken and immediately stored at −20°C.…”
Section: Methodsmentioning
confidence: 99%
“…For UV radiation, an Oriel solar simulator (Oriel Instruments, Stratford, CT, USA, 1000 W UV Solar Simulator, 8 · 8 inch beam size, Model: 91294, Newport, linaer UV spectrum Fig. Suction blister fluids that have been proven as a valuable source for the study of soluble biomarkers (22,23) were raised immediately and 24 h after irradiation, as described (24)(25)(26). The individual minimal erythema dose (MED) was determined in a defined area on the volar forearms (2 · 4 cm).…”
Section: Generation Of Suction Blister Fluidsmentioning
confidence: 99%